Static antibiotic loaded cement spacer application in 2-stage management of native and prosthetic hip joint infections: a case series and review of the literature - Ayekoloye, Charles I.; Balogun, Mosimabale J.; Alonge, Temitope O. (International Journal of Research in Orthopaedics, 2025)
Two-stage revision including interval cement spacer application is the gold standard treatment for both prosthetic and native hip infection with joint destruction. We present a summarised case series of our experience of successfully treating 8 infected joints in 6 patients treated with 2-stage revision using interval static spacers. Two patients with 3 native joint infections and 4 patients with 5 prosthetic joint infections were treated with 2-stage arthroplasty with interval static spacer application consisting of static block spacers or cement beads. There were 2 females and 4 males. Mean age is 40.5 years and range 24-60 years. Mean interval between the first and second stage is 8weeks. One case has not undergone the second stage as he is unable to fund the operation. Organisms cultured include methicillin- sensitive staphylococcus aureus, enterococcus. All underwent cementless hip reconstruction with one patient undergoing hybrid hip reconstruction. At mean 36-month follow-up (range 30-44 months) all patients have normalized inflammatory markers and improvement in Oxford hip score (OHS) from pre-operative mean 16.6 (range 15-19) and post-operative mean OHS 43.7 (range 35-50). Patients continue to be followed up. We recommend this cement spacer option as part of a 2-stage procedure when faced with moderate to severe acetabular bone loss. It is effective in treating native or prosthetic hip joint infections and joint infections in patients with sickle cell haemoglobinopathy.